Social distress and economic integration - Walter Hyll; Lutz Schneider (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2016)
We analyze whether social distress from income comparisons affects attitudes towards the integration of economies. Using Germany's division as natural experiment, we find that East Germans' feelings of relative deprivation with respect to better-off West Germans led to significantly more support for the upcoming German re-unification.
urn:nbn:de:gbv:3:2-57823
Keywords: D31; F15; 330; relative deprivation; economic integration; merger of populations; social comparisons; natural experiment